SISTEM PENJAMINAN MUTU TERPADU MANAJEMEN PENDIDIKAN - Nur Alim (IAI DDI POLEWALI MANDAR, 2024)
This study discusses the integrated quality assurance system of education management. The study’s problems are about measuring quality control systems, achievement strategies, and educational quality assurance systems. This research is library research using a deductive mindset. Data analysis was carried out through 3 stages: 1) Data reduction, 2) Data presentation, and 3) Verification and drawing conclusions. The integrated quality control measurements include 1) Precontrol-Feedfowerd, 2) Concurrent Control, and 3) Feedback Control. The strategy for achieving the quality of education in Indonesia is contained in achieving the national education goals which are mandated by Law no. 20 of 2003 concerning the National Education System. The quality assurance system has the function of controlling the implementation of education by educational units to realize quality education. The quality assurance system for primary and secondary education consists of an internal and external quality assurance systems for primary and secondary education.